The Cognitive Emotion Regulation Questionnaire (CERQ): The Evaluation of Structural and Convergent Validity on a Serbian Sample - Ilić, Mihajlo; Rakočević, Nikolija; Žuljević, Dragan (Psihološka istraživanja, 2025)
The current research is aimed at examining the psychometric properties, i.e. the structural and convergent validity of the Cognitive Emotion Regulation Questionnaire (CERQ) translated into Serbian through two independent and consequent studies. In Study 1, conducted on the sample of 674 young adults (Mage = 19.68, SD = 1.29), the structural validity of the CERQ was evaluated by testing the theoretically based nine-component structure using the methods of confirmatory factor analysis and exploratory structural equation modelling. Study 2 was aimed at retesting the model obtained in the previous study on the sample of 703 participants (Mage = 22.96, SD = 7.05). In addition, convergent validity of the CERQ was examined by the correlation with the measures of positive and negative affect, life satisfaction, and general distress. The results support the CERQ as a reliable and valid measure of the cognitive emotion regulation strategies. The latent structure of the questionnaire is best described by a nine-factor model defined by the original instrument. In both of our samples, the dimension of Positive reformulation has demonstrated the same structural specificities, suggesting the need for additional checking of both the instrument itself and the specificities of the cognitive emotion regulation strategies in our cultural area. The findings of these studies also indicate usefulness of exploratory structural equation modelling compared to the traditional methods of confirmatory factor analysis in the investigation of the latent structure of the CERQ.